Meningkatkan Motivasi Peserta Didik Baca Tulis Al-Qur’an Melalui Metode Numbered Head Together - Komala Dewi, Puspita; Fadilah, Raghil; Weri Laras Mita, Reginas; Aini Farida, Nur; M.Makbul (Universitas Majalengka, 2024)
The aim of this classroom action research is to increase students' motivation to pay more attention to their ability to read and write the Al-Quran. The inhibiting factor is students' lack of awareness of their ability to read and write the Koran. The research was taken using qualitative descriptive. The results of this research indicate that the process of learning to read and write the Al-Quran has not been fully implemented because the learning method used is not appropriate. To increase motivation to read and write the Al-Quran in this classroom action research, researchers used the Numbered Head Together learning model, which is a learning model that prioritizes the learning process to encourage students to participate actively in groups. This learning model also requires students to complete the Numbered Head Together learning steps, namely: numbering, asking questions, group discussions, and group discussions about the results.